2002
DOI: 10.1073/pnas.212532699
|View full text |Cite
|
Sign up to set email alerts
|

Mutations that permit efficient replication of hepatitis C virus RNA in Huh-7 cells prevent productive replication in chimpanzees

Abstract: The development of a subgenomic replicon derived from the hepatitis C virus (HCV) strain Con1 enabled the study of viral RNA replication in Huh-7 cells. The level of replication of replicons, as well as full-length Con1 genomes, increased significantly by a combination of two adaptive mutations in NS3 (E1202G and T1280I) and a single mutation in NS5A (S2197P). However, these cell culture-adaptive mutations influenced in vivo infectivity. After intrahepatic transfection of chimpanzees, the wild-type Con1 genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(198 citation statements)
references
References 43 publications
12
183
1
2
Order By: Relevance
“…Measurement of HCVpp entry may be more quantitative, since only a single round of infection can occur, but the incorporation of E2 and apolipoproteins into HCVcc virions may be more similar to natural HCV virions. It is important to note, however, that some studies have shown that HCVcc particles produced in Huh-7 cells also differ from HCV particles produced in vivo or in primary human hepatocytes in their biophysical properties (Lindenbach et al, 2006;Podevin et al, 2010), and that mutations that enhance HCVcc replication in vitro can reduce efficient replication in animal models (Bukh et al, 2002). Measurement of specific infectivity in both systems is also potentially complicated by the presence of viral RNA that is not associated with authentic virions.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of HCVpp entry may be more quantitative, since only a single round of infection can occur, but the incorporation of E2 and apolipoproteins into HCVcc virions may be more similar to natural HCV virions. It is important to note, however, that some studies have shown that HCVcc particles produced in Huh-7 cells also differ from HCV particles produced in vivo or in primary human hepatocytes in their biophysical properties (Lindenbach et al, 2006;Podevin et al, 2010), and that mutations that enhance HCVcc replication in vitro can reduce efficient replication in animal models (Bukh et al, 2002). Measurement of specific infectivity in both systems is also potentially complicated by the presence of viral RNA that is not associated with authentic virions.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the idea that Huh-7 cells might be unable to support HCV particle assembly or release. However, culture-adaptive changes were also found to be lethal or highly attenuating for replication in chimpanzees 95 . This suggested that adaptive mutations promoting efficient RNA replication in cell culture might preclude production of infectious particles.…”
Section: Completing the Virus Life Cycle: Extracellular Virionsmentioning
confidence: 98%
“…However, this remains to be seen, and it should be noted that some cell culture adaptive mutations selected in replicons are not tolerated in full length HCV genomes following intrahepatic inoculation into chimpanzees. 25 Moreover, these results contain lessons to guide further optimization of protease inhibitors.…”
Section: Commentsmentioning
confidence: 98%